Aseptic Technique - Monica Lypson; Stacie Buckler; Kelly Poszywak (Association of American Medical Colleges, 2015)
Abstract Introduction To adequately address local infections, wounds must be properly incised and drained, a common procedure that learners perform when the site for location is uncomplicated. Learners must perform this procedure using aseptic technique. Aseptic technique refers to practices that are followed to prevent contamination by microorganisms. The use and proper donning of sterile gloves are key components to properly performing aseptic technique. In this exercise, we present a mock incision and drainage using a standardized patient (SP) to assess aseptic technique as well as communication with SPs and other health professions. Methods This 20-minute case includes exposure to some of the Joint Commission's National Patient Safety Goals and to an SP with a mock abscess. The SP presents with an abscess on the arm that needs to be assessed and opened. Depending on the facilitator's decision, either the SP or an observer, a mock registered nurse, completes an aseptic technique checklist. The learner prepares the area and performs the procedure up to the actual incision. At that point, the learner is instructed to dress the wound as if drained and complete the task as outlined. Upon completion, each learner receives a copy of the checklist and supplemental materials on aseptic technique, hand washing, and skin preparation to reinforce concepts assigned. Results A comparison of novices and experts produced the following findings. For reliability, the internal consistency of the checklist for each of the two raters was .87 and .71 (Cronbach's alpha); interrater reliability using the intraclass correlation coefficient was .74 (p < .001) for the global scale. For validity, operating room nurses outperformed students on the global scale (t = 7.47, p < .0001, and t = 10.66, p < .0001, for the two raters, respectively) and on several checklist items. The effect-size values for raters were large (Cohen's d = 3.0 and 4.4), providing validity evidence for the ability of this assessment to detect difference in performance of this task. Discussion Programs may want to consider using a validated instrument to check competence given that appropriate use of aseptic technique frequently occurs in the context of unsupervised activities. More work is needed to enhance resident skills in the area of aseptic technique because of limited improvement despite additional clinical experience.